Extraction of polyphenol from phyllanthus niruri - Kee, Keing Lee (2017)
Phyllanthus niruri which is also known as Dukung Anak is a plant which contain miscellaneous bioactive components which provide the medical effects such as antioxidant, anti-cancer and treating Hepatitis-B. Extraction is a common method to obtain bioactive component from plant materials therefore this research is to elucidate the effect of solvents types and investigate the performance of different type extraction method on P.Niruri. Ultrasonic assisted extraction and microwave assisted extraction methods were studied because there is no previous work found in literature. Analysis such as Total Phenolic Content, Total Flavonoids Content, Ultra-Performance Liquid Chromatography were carried out throughout the research. From the works, it is found that highest yield of phyllanthin with 4.56mg Phy/g DW was obtained with 20% aqueous Isopropanol whereas the quercetin with the highest yield, 10.14mg Que/g DW in 20% aqueous ethanol and the highest yield 15.44mg GAE/g DW of gallic acid was obtained by using water. Central Composite Design analysis shown that microware assisted extraction with 250W power, 3.62 minutes and 52.58% ethanol concentration obtain the optimum yield of polyphenol extraction of 83.70%. In conclusion, the yield of bioactive component is highly dependent on solvent polarity used in extraction and microwave extraction method provides a fast extraction without significantly compromising the extraction yield compare to ultrasonic assisted extraction.